Achieving ultrahigh power factor in Mg3(Sb,Bi)2-based thermoelectric alloys sintered by introducing elemental Mg and W - Liangsheng Wang; Shunjian Xu; Jian Yang; Xinyu Tang; Xinyu Wang; Guanjun Qiao; Guiwu Liu (Journal of Advanced Ceramics)
Improving the power factor (PF) of thermoelectric materials is crucial for increasing the output power density and broadening practical applications. The near-room-temperature electrical performance of Mg3(Sb,Bi)2-based alloys is hindered due to the presence of Mg vacancies and grain boundary scattering, resulting in a lower power factor. In this study, we introduced excess Mg into Mg3(Sb,Bi)2 alloy during the hot-pressing process, triggering a liquid phase sintering process, which can effectively fill the Mg vacancies and increase the average grain size (Dave) to significantly reduce grain boundary scattering. This leads to enhanced room-temperature electrical conductivity (σ) without detrimental effects on the Seebeck coefficient (S), thus yielding a high average PF of ~25.3 μW·cm−1·K−2 and an average figure of merit (ZT) of ~1.03 within the temperature range of 323‒623 K. Moreover, different amounts of W were further added, and density-functional theory (DFT) calculations reveal that W segregation at grain boundaries (GBs) reduces interfacial potential barriers, leading to improved S and σ. Consequently, an ultrahigh average PF of ~26.2 μW·cm−1·K−2 was attained in the W0.06Mg3.2Sb1.5Bi0.49Te0.01–4% Mg alloys. Additionally, the mechanical properties (Vickers hardness and fracture toughness) were also enhanced compared with those of the pristine Mg3(Sb,Bi)2 alloy. This dual-modified approach can significantly boost the TE performance and mechanical stability, advancing Mg3(Sb,Bi)2-based materials for practical applications.